Energy systems : adaptive complexity - Ohta, Tokio (Elsevier Science, 2000)
This book consists mainly of revised versions of the papers presented at the "Energy Systems and Technologies: as Approached from Adaptive Complexity" symposium sessions during the 4th International Conference on "New Energy Systems and Conversions" (20-30 June 1999; Osaka University, Japan), as well as some pertinent additional research reports. In order to realise the adaptive complexity of a system, it is necessary to know the energy conversion mechanisms of the media. This book details a wide range of situations in which adaptive complexity can be applied and found, from predicting air-flow in a room to describing turbulence as a complex system. The idea of approaching both the study of energy systems and energy technologies from the adaptive complexity aspect is new, and still a very much developing field. These pioneering articles discuss not only previous, but also pending problems